A qualitative exploration of patient and healthcare professionals' views and experiences of palliative rehabilitation during advanced lung cancer treatment. (December 2018) - Payne, Cathy; McIlfatrick, Sonja; Larkin, Philip; Dunwoody, Lynn; Gracey, Jackie
Background: Limited evidence exists on the impact of palliative rehabilitation during systemic treatment of advanced cancer. Aim: To explore the experiences and perceptions of patients and healthcare professionals on the feasibility and acceptability of palliative rehabilitation during advanced lung cancer treatment. Design: Qualitative design using individual semi-structured interviews transcribed verbatim and analysed thematically. Setting/participants: Eight patients and six healthcare professionals were recruited from a regional cancer centre in the United Kingdom following completion of a 6-week individualised behaviour change study which combined physical activity and nutritional guidance. Results: Palliative rehabilitation and study participation were positively viewed by both participants and healthcare professionals. Five themes were identified from patient interviews within an overarching theme of living with and beyond an advanced cancer diagnosis: (1) challenges of living with incurable cancer, (2) personal and altruistic reasons for participating in rehabilitation, (3) applicability of palliative rehabilitation content, (4) barriers and facilitators to adherence and (5) positive impact on self and others. Three themes were identified from healthcare professionals, within an overarching theme of palliative rehabilitation: exploring the concept (1) pre-study-mixed perceptions of palliative rehabilitation, (2) perceived benefits for patients and families and (3) lessons for future research. Conclusion: Patients described personal benefits associated with setting their own goals for physical activity and dietary intake. Healthcare professionals who initially expressed a negative or indifferent stance towards palliative rehabilitation, displayed a mind-set change and were keen to explore further opportunities to expand the evidence base.